2016
DOI: 10.1128/aem.04044-15
|View full text |Cite
|
Sign up to set email alerts
|

Feeding of Enterococcus faecium NCIMB 10415 Leads to Intestinal miRNA-423-5p-Induced Regulation of Immune-Relevant Genes

Abstract: bProbiotics are widely used in human and animal health, but little is known about the mode of action of probiotics. One possible mechanism at the molecular level could be an influence on microRNAs (miRNAs) and the related immune-relevant target genes. Here, we analyzed differential expression of miRNA and potential target genes of ileal and jejunal lymphatic tissues from Enterococcus faecium NCIMB 10415-fed piglets versus untreated controls by using next-generation sequencing. We identified miR-423-5p as being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 37 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…The main datum reveals a 2.11-fold increase of miR 423-5p and the related downregulation of the immune-relevant immunoglobulin lambda light C region (IGLC) and immunoglobulin kappa constant (IGKC) target genes [85]. On the same direction, Veltman et al profiled miRs from T84 monolayers before and after co-incubation with E. coli Nissle 1917.…”
Section: Gut Microbiota and Mirs Modulation: From Association To Causmentioning
confidence: 99%
“…The main datum reveals a 2.11-fold increase of miR 423-5p and the related downregulation of the immune-relevant immunoglobulin lambda light C region (IGLC) and immunoglobulin kappa constant (IGKC) target genes [85]. On the same direction, Veltman et al profiled miRs from T84 monolayers before and after co-incubation with E. coli Nissle 1917.…”
Section: Gut Microbiota and Mirs Modulation: From Association To Causmentioning
confidence: 99%
“…Heat-treated L. paracasei NCC 2461 downregulated miR-27a in peripheral blood mononuclear cells [32]. Enterococcus faecium NCIMB 10415 upregulated miR-423-5p and downregulated its target gene IGLC (immunoglobulin lambda light C region) in the intestine of piglets [33]. These studies show that different probiotics elicit different miRNA responses.…”
Section: Discussionmentioning
confidence: 79%
“…They found that feeding E. faecium affected the expression of miR-423-5p as well as regulating its target gene IGLC. Therefore, E. faecium bene ts the immune cells in the small intestine probably by affecting the expression of miR-423-5p [175].…”
Section: Modulation Of Microrna By Probioticsmentioning
confidence: 99%